(untitled) (Research, Society and Development, 2021)
Objective: To present the relationship of SARS-CoV-2 hair infection as pulmonary thromboembolism, also evidencing, at the same time, two non-auxiliary imaging tests for the diagnosis of this pathology, emphasizing the main techniques used, such as: Radiography, Computerized Tomography and Angiography Pulmonary. Methodology: O present study is about an integrative review of descriptive and qualitative literature, based on electronic databases Centers for Disease Control and Prevention (CDC), Scientific Electronic Library Online (SciELO), PubMed (MEDLINE), included foram Articles published exclusively in the year 2020. Results and Discussion: COVID-19 is a respiratory viral infection that can evolve to cause thrombotic disease or formation of thromboembolism, it is associated with an increase in chemokines and pro-inflammatory cytokines, which leads to an increase in vascular permeability, among others. Due to the incidence of thrombotic diseases in patients with novo coronavirus, imaging exams were used, within them, or X-ray and chest CT, showing less obvious results. Contudo, CT shows higher specificity and sensitivity compared to X-ray. Conclusion: It is concluded that COVID-19 causes haematological alterations that predispose to the formation of thromboembolism, due to its facial alterations it is necessary to use two examinations per image, being essential for a confirmation of diagnosis.